(untitled) (Indian Journal of Public Health Research & Development, 2023)
Abstract Background: Cancer is a major burden and threat to global society. It is one of the leading causes of death in both developed and developing countries. The main modalities used for its treatment include surgery, radiation, chemotherapy, immunotherapy, and hormones. Materials & Methods: The current study was performed to find incidence of chemotherapy induced eosinopillia in patients with different cancers who were receiving standard chemotherapy regimens (minimum two cycles and maximum six to eight cycles). Total leucocyte count, absolute eosinophil count and differential leucocyte count was done just before starting of chemotherapy. Differential leucocyte count (DLC) was reported after 1st cycle of chemotherapy agents, before last dose of chemotherapy, after 6 weeks of completion of chemotherapy, and after six month of completion of chemotherapy to see the changes on eosinophil counts. Results: Most commonly used anticancer agents were 5 FU 61 (61%), doxorubicin 43 (43%), cyclophosphomide 53 (53%), cisplatin 10 (10%), paclitaxel 20 (20%), carboplatin 25 (25%), gemcitabine 11 (11%), oxaliplatin 14 (14%) and capecitabine 11 (11%). The pre-CT eosinophil count had a mean of 3.41 (range, 2 to 4) and post-CT after 1st dose had a mean of 5.06 (range, 3 to 8) (p <0.0001). The pre-CT eosinophil count had a mean of 3.41 (range, 2 to 4) and post-CT after 6 months of chemotherapy had a mean of 6.85 (range, 5 to 8) (p <0.0001). Increased eosinophil count after 1st dose and 6 months completion of chemotherapy was highly significant from baseline values (P < 0.0001). Conclusion: Study has generated a hypothesis that administration of many anticancer agents may increase eosinophil count or peripheral eosinophilia. Additional large scale prospective studies must be performed to confirm our results.